Agility, innovation and impact: pedestrian safety walkway intervention in Kajang, Malaysia - K. C. Mani, Kulanthayan; Karrupiah, Karmegam; A. Rahman, Anita (2016)
Child pedestrian as a vulnerable group around the school area needs intervention to address their problem as their risk is high for sharing the roadway with vehicles. The problem here was high traffic volume with speed enough to be dangerous for children who are exposed in the open. Thus to reduce the child pedestrian risk on road, a pedestrian safety walkway intervention was mooted and grant proposals were bidded and successfully obtained from donors. This resulted in the birth of a Pedestrian Safety Walkway with the aim of segregating the pedestrian from the vehicles whom are using the same roadway.